Landscape-Scale Effects of Irrigation on a Dry Cereal Farmland Bird Community - Giralt, David; Pantoja, Javiera; Morales, Manuel B.; Traba, Juan; Bota, Gerard (Frontiers in Ecology and Evolution, 2021)
Landscape modification and habitat fragmentation are one of the major current threats to biodiversity. The main source of habitat fragmentation is the loss of focal habitat area, but changes in the composition of the surrounding landscape also have a direct effect on biodiversity. These changes may lead to the loss of some species but also may favour species replacement. Farmland birds in Europe are affected by landscape changes due to farmland intensification, such as the spread of irrigation, which may occur at different spatial scales. As irrigation is expected to increase in the coming years, producing landscape changes which may affect protected areas, it is necessary to evaluate its potential consequences over focal biodiversity. In this study we assess the relationship between the increase of irrigated land at different spatial scales and changes in a dry cereal farmland bird community, bird abundance and species richness, using generalized (GLM). We used a dry cereal farmland affinity index to describe the level of community specificity for dry cereal farmland. The increase in irrigated tree orchards surface produced an increase in total bird abundance and species richness even at long distance, while had a negative effect on the dry cereal farmland bird community, and thus a replacement of specialist by generalist species. On the contrary, an increase of the surface of irrigated herbaceous within a maximum distance of 500 m favoured the dry cereal farmland bird community. Our results show the importance of landscape-scale effects of irrigation occurring outside protected areas on the farmland bird community inside Nature 2000 sites, as well as how these effects are detected even at long distance (2000 m) from the disturbance source.